2016
DOI: 10.1186/s12966-016-0440-4
|View full text |Cite
|
Sign up to set email alerts
|

The influence of socio-demographic, psychological and knowledge-related variables alongside perceived cooking and food skills abilities in the prediction of diet quality in adults: a nationally representative cross-sectional study

Abstract: BackgroundInterventions to increase cooking skills (CS) and food skills (FS) as a route to improving overall diet are popular within public health. This study tested a comprehensive model of diet quality by assessing the influence of socio-demographic, knowledge- and psychological-related variables alongside perceived CS and FS abilities. The correspondence of two measures of diet quality further validated the Eating Choices Index (ECI) for use in quantitative research.MethodsA cross-sectional survey was condu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

14
128
1
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 108 publications
(161 citation statements)
references
References 43 publications
14
128
1
3
Order By: Relevance
“…Many young adults lack knowledge and skills around food and nutrition. In the UK, young adults aged 18 to 40 years have less confidence in different foods and cooking methods and poorer nutrition knowledge compared with their older counterparts …”
Section: Mediatorsmentioning
confidence: 99%
“…Many young adults lack knowledge and skills around food and nutrition. In the UK, young adults aged 18 to 40 years have less confidence in different foods and cooking methods and poorer nutrition knowledge compared with their older counterparts …”
Section: Mediatorsmentioning
confidence: 99%
“…Several studies have found improvements in the psychosocial factors, knowledge, and intentions, as well as diet, following behavior change interventions (Anderson, Winett, & Wojcik, 2007; Kramer et al, 2012; Luszczynska, Gibbons, Piko, & Tekozel, 2004; Suratkar et al, 2010). Among low-income African-American populations, there is still a limited understanding of the relation between adult psychosocial factors, and food-purchasing and food preparation patterns (Gustat et al, 2017; McGowan et al, 2016). …”
mentioning
confidence: 99%
“…Alguns estudos têm encontrado que as escolhas alimentares mais saudáveis se tornam mais fortes conforme aumenta a idade, embora publicações avaliando as escolhas alimentares de acordo com a idade não sejam tão frequentes (KEARNEY et al, 2001;NAUGHTON et al, 2015;MCGOWAN et al, 2016 (MARDON et al, 2015). Também para a amostra total do presente estudo, quem não tinha filho declarou escolher mais por Preferência, Prazer, Socialização, Atração…”
Section: Motivações Para Comer Segundo a Idadeunclassified
“…Maiores habilidades culinárias, definidas como conjunto de habilidades mecânicas e físicas utilizadas na preparação de refeições -como cortar, misturar, colocar pra cozinhar -e também planejamento, organização e habilidades conceituais e perceptivas sobre as mudanças dos alimentos quando cozidos, é tipicamente associado com melhor qualidade da dieta, incluindo maior consumo de frutas e vegetais e menor consumo de produtos industrializados e prontos para consumo (WOLFSON e BLEICH, 2015;MCGOWAN et al, 2016;WILSON et al, 2017). Cozinhar, portanto, é um fator individual e modificável que tem relação com as escolhas alimentares.…”
Section: Motivações Para Comer Segundo Cozinhar Ou Nãounclassified
See 1 more Smart Citation